Persistence and adherence to overactive bladder medications in Japan: A large nationwide real‐world analysis. (22nd August 2017) - Kato, Daisuke; Uno, Satoshi; Van Schyndle, James; Fan, Alan; Kimura, Tomomi
Abstract : Objectives: To evaluate persistence and adherence to mirabegron and antimuscarinics in Japan using data from two administrative databases. Methods: The present retrospective study evaluated insurance claims for employees and dependents aged ≤75 years, and pharmacy claims for outpatients. From October 2012 to September 2014, new users of mirabegron or five individual antimuscarinics indicated for overactive bladder in Japan (fesoterodine, imidafenacin, propiverine, solifenacin and tolterodine) were identified and followed for 1 year. Persistence with mirabegron and antimuscarinics were evaluated using Kaplan–Meier methods. Any associations between baseline characteristics (age, sex and previous medication use) and persistence were explored. Adherence was assessed using the medication possession ratio. Results: In total, 3970 and 16 648 patients were included from the insurance and pharmacy claims databases, respectively. Mirabegron treatment was associated with longer median persistence compared with antimuscarinics (insurance claims: 44 [95% confidence intervals 37–56] vs 21 [14–28] to 30 [30–33] days, pharmacy claims: 105 [96–113] vs 62 [56–77] to 84 [77–86] days). The results were consistent when patients were stratified by age, sex and previous medication. Persistence rate at 1 year was higher for mirabegron (insurance claims: 14.0% [11.5–16.8%] vs 5.4% [4.1–7.0%] to 9.1% [5.3–14.2%], pharmacy claims: 25.9% [24.6–27.3%] vs 16.3% [14.0–18.6%] to 21.3% [20.2–22.4%]). Compared with each antimuscarinic, a higher proportion of mirabegron‐treated patients had medication possession ratios ≥0.8. Conclusions: This large nationwide Japanese study shows that persistence and adherence are greater with mirabegron compared with five antimuscarinics.